2016
DOI: 10.1002/2016gl070466
|View full text |Cite
|
Sign up to set email alerts
|

Decaying shock studies of phase transitions in MgO‐SiO2 systems: Implications for the super‐Earths' interiors

Abstract: We report an experimental study of the phase diagrams of MgO, MgSiO3, and Mg2SiO4 at high pressures. We measured the shock compression response, including pressure‐temperature Hugoniot curves of MgO, MgSiO3, and Mg2SiO4 between 0.2–1.2 TPa, 0.12–0.5 TPa, and 0.2–0.85 TPa, respectively, using laser‐driven decaying shocks. A melting signature has been observed in MgO at 0.47 ± 0.04 TPa and 9860 ± 810 K, while no such phase changes were observed either in MgSiO3 or in Mg2SiO4. Increases of reflectivity of MgO, Mg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
77
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 45 publications
10
77
1
2
Order By: Relevance
“…Their shock reflectivity measurements were done at two wavelengths, 532 and 1064 nm. Despite all these improvements, Bolis et al [23] observed largely the same main features of MgO already reported by McWilliams et al [22]. Yet, they attributed the large light intensity increase encountered during shock decay, attributed by McWilliams et al to the B2 to B1 solid-solid transition, instead to a transition from melt to B2.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…Their shock reflectivity measurements were done at two wavelengths, 532 and 1064 nm. Despite all these improvements, Bolis et al [23] observed largely the same main features of MgO already reported by McWilliams et al [22]. Yet, they attributed the large light intensity increase encountered during shock decay, attributed by McWilliams et al to the B2 to B1 solid-solid transition, instead to a transition from melt to B2.…”
Section: Introductionmentioning
confidence: 70%
“…Upon compression along its principal Hugoniot, MgO goes from the B1 (NaCl structure) solid phase into the B2 (CsCl structure) solid phase, then into the B2-liquid coexistence region, and finally reaches the pure liquid phase above approximately 620-700 GPa [18,21]. Interpolation between the melting points measured for B1 phase at the highest attainable static pressure of ≈40 GPa [3,4] and those measured for B2 phase at approximately 470 to 650 GPa [22,23] or ≈700 GPa [21] is subject to large errors comparable to the scatter between various theoretical predictions.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations